Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Pertumbuhan Ekonomi Provinsi Sumatera Selatan 2014-2018 - Endang Kusdiah Ningsih; Dwi Eka Noviaty (Ekonomis: Journal of Economics and Business, 2019)
The purpose of this study is to prove empirically the effect of Regional Own-Source Revenue and Balanced Funds to economics growth in province of South Sumatera. The data used is   secondary data during 2014-2018 from  Central Statatistics Agency (BPS) and Report of Economics and Finance  (KEK). Methods of data analysis in this study is to use multiple linear regression analysis. The result showed that of Regional Own-Source Revenue and Balanced Funds has significant effect to economics growth simultaneously. As partialy, Regional Own-Source Revenue  has significant effect to economics groth, and Balanced Funds has not significant effect to economics growth.